Festschrift in honor of Norman K. Denzin : he knew his song well - Chen, Shing-Ling S. (Studies in symbolic interaction, 2022)
Due to his major contributions in qualitative inquiries, Norman K. Denzin is regarded as 'the Father of Qualitative Inquiries.'Festschrift in Honor of Norman K. Denzin: He Knew His Song Well, Volume 55 of Studies in Symbolic Interaction, is a compilation of writings published in his honor. Featuring chapters which detail Denzin's unrivalled contributions to qualitative inquiries, the authors describe the immense scope of Denzin's qualitative research, from symbolic interactionism and postmodernism to justice studies. Documenting Denzin's inclusive efforts to embrace various perspectives in qualitative inquiries to advance the mission of qualitative research, this edited collection chronicles Denzin's continuous efforts in nurturing the field of qualitative inquiries via editorship and conference organization, fostering generations of qualitative researchers around the world. This collection is a comprehensive and compelling read for students and academics interested in qualitative research who wish to chart the impressive impact that Norman K. Denzin's work has had on the field.